Collagen as a Bioactive Ingredient in Nutricosmetology - A Review - Kozik, Wiktoria; Polak-Bielawska, Dagmara; Kutaj, Aleksandra; Savitskaya, Tatyana (Quality in Sport, 2025)
Introduction and Purpose Collagen is a major structural protein responsible for maintaining the strength and elasticity of the skin, hair, and nails. Its synthesis decreases with age, leading to visible signs of aging. Nutricosmetology focuses on supporting these processes through nutrition and supplementation. The aim of this review was to analyze the role of collagen as a nutraceutical ingredient and to assess the evidence on its effectiveness in supporting the condition of the skin, hair, and nails. Materials and Methods This narrative review was based on scientific publications from PubMed and Google Scholar (2015–2025) addressing the structure, biological functions, and dietary sources of collagen, as well as clinical studies evaluating the effects of collagen supplementation. Description of the State of Knowledge Evidence indicates that hydrolyzed collagen supplementation (2.5-10 g/day for 8-12 weeks) improves skin hydration, elasticity, and density, reduces wrinkles, and strengthens hair and nails. Marine collagen demonstrates the highest bioavailability and safety. The effectiveness of supplementation increases when combined with vitamin C and trace elements such as zinc, copper, and manganese. Conclusions Collagen supplementation effectively supports regenerative and anti-aging processes in the skin and its appendages by providing amino acids essential for collagen fiber synthesis and stimulating fibroblast activity. Further studies are needed to compare long-term efficacy across different collagen sources and demographic groups.